CDDO-Me Attenuates Astroglial Autophagy via Nrf2-, ERK1/2-SP1- and Src-CK2-PTEN-PI3K/AKT-Mediated Signaling Pathways in the Hippocampus of Chronic Epilepsy Rats - Ji-Eun Kim; Tae-Cheon Kang (MDPI AG, 2021)
Clasmatodendrosis is an autophagic astroglial death showing extensive swollen cell bodies with vacuoles and disintegrated/beaded processes. This astroglial degeneration is closely relevant to the synchronous epileptiform discharges. However, the underlying molecular mechanisms and the roles of clasmatodendrosis in spontaneous seizure activity are still unknown. The 2-cyano-3,12-dioxo-oleana-1,9(11)-dien-28-oic acid methyl ester (CDDO-Me; RTA 402) is one of the activators for nuclear factor-erythroid 2-related factor 2 (Nrf2) that is a redox-sensitive transcription factor. In the present study, we explored the effects of CDDO-Me on clasmatodendrosis in chronic epilepsy rats, which could prevent epilepsy-related complications. In the present study, clasmatodendritic astrocytes showed reduced Nrf2 expression and its nuclear accumulation, which were restored by CDDO-Me. CDDO-Me also abrogated heat shock protein 25 (HSP25) upregulation in clasmatodendritic astrocytes by regulating extracellular signal-related kinases 1/2 (ERK1/2)-specificity protein 1 (SP1)- and Src-casein kinase 2 (CK2)-phosphatase and tensin homolog deleted on chromosome 10 (PTEN)-phosphatidylinositol-3-kinase (PI3K)-AKT-glycogen synthase kinase 3β (GSK3β)-bax-interacting factor 1 (Bif-1)-mediated signaling pathways in chronic epilepsy rats. In addition, CDDO-Me ameliorated spontaneous seizure duration, but not seizure frequency and behavioral seizure severity. Therefore, our findings suggest that clasmatodendrosis may affect seizure duration in chronic epilepsy rats, and that CDDO-Me may attenuate autophagic astroglial degeneration by regulating various signaling pathways.